George Thomas deed - Thomas, George, active 1726.
Copy of a deed for land in Charles County, Md., sold by George Thomas to James Peale.
Handwritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Peale, James, -- active 1726.; Deeds -- Maryland -- Charles County